LEGAL PROTECTION OF THE ORIGINAL CERTIFICATE OWNER ON THE ISSUANCE OF A SUBSTITUTE CERTIFICATE THAT IS AGAINST THE LAW - Sari Wahyuni Amanda; Enny Koeswarni (Awang Long Law Review, 2022)
The purpose of the issuance of a replacement certificate is to replace the damaged certificate of land rights caused by accidental damage due to natural disasters or damage due to aging paper or the certificate being torn due to the carelessness of the holder, which causes the certificate to be unusable. The problem in this research is how is the legal protection of the owner of the original certificate for the issuance of a replacement certificate against the law by the Land Office of Semarang City? The research method used is normative juridical using secondary data and analyzed using qualitative methods. The results of the study show that the legal protection of the owner of the original certificate for the issuance of a substitute certificate against the law by the Land Office of the City of Semarang is divided into 2 (two), namely preventive legal protection through deliberation between the holder of land rights and also as a plaintiff with the Land Office of the City of Semarang before taken through the Court which has been regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases which aims to provide legal certainty and justice regarding the control, ownership, use and utilization of land. The second legal protection is repressive through a lawsuit to cancel the decision of the Head of the Land Office of Semarang City to the State Administrative Court and also a lawsuit against the law to the District Court.